Dominantly inherited Alzheimer disease: Frequency, genetic heterogeneity, and clinical phenotype in Latin America: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Guerra, Jorge J Llibre; Mendez, Patricio Alexis Chrem; Allegri, Ricardo F.; Surace, Ezequiel; Llibre‐Rodriguez, Juan; Ibarrola, Mariana Longoria; Cornejo‐Olivas, Mari; Sosa‐Ortíz, Ana Luisa; Takada, Leonel Tadao; Lopera, Francisco; Sanchez, Victor; Jiménez‐Velazquez, Ivonne Z.; et al.
Abstract: Background: More than 300 pathogenic variants in APP, PSEN1 and PSEN2 genes have been reported causing Dominant Inhered Alzheimer Disease (DIAD); most of these reports come from Northern hemisphere countries. In recent years, a growing number of familial AD cases have become known in Central and South American countries; however, little is known about epidemiology and clinical‐genetic profile of DIAD in Latin American (LatAm) countries. We aimed to systematically review and describe DIAD cases reported in LatAm populations. Method: A systematic review for all DIAD cases reported in LatAm was completed between September 2019 to December 2019. The search strategy included the following major databases: MedLine, SciELO, Cochrane, and LILACS. More than 927 records were screened and 106 peer‐reviewed publications on DIAD families from LATAM were included in the final analysis. We extracted individual‐level data on the age at onset(AAO), disease course, and the presence/absence of neurological findings. Findings extracted from literature were updated by local researchers . The combined dataset included 843 family members, of whom 237 were affected by DIAD. Analyses were done using descriptive statistics, comparisons of means and frequencies. Result: 24 DIAD pathogenic variants have been reported in LatAm countries, including 21 PSEN1, two PSEN2 and one APP variant . Countries with higher DIAD frequency were Colombia, Puerto Rico, Mexico, and Cuba, usually related to founders' effects on these regions. AAO differed by causing gene, with a younger age at onset for individuals harboring PSEN1 variants, followed by APP and PSEN2 carriers (43.8 ± 8.9 years vs 48.6 ± 1.6 years vs 52.2 ± 2.1 years respectively, p < 0.0001). The most common clinical presentation was amnestic. Atypical features were described with M146V‐ PSEN1 (Argentina) and A431E‐ PSEN1 (Mexico) presenting with FTD‐like syndrome and spastic paraparesis respectively. We found that affected individuals carrying PSEN1 mutations also experience myoclonus, pyramidal, and cerebellar signs (p < 0.001, p = 0.002, and p = 0.003, respectively). Conclusion: This work describes an initial overview of DIAD in LatAm. The discovery and clinical characterization of DIAD families from Lain America will inform the development of the DIAN‐observational study in the region and will create a cohort ready population for clinical the upcoming trials.